<span>6/3+(-1/3)
</span><span>= 6/3-1/3
= 5/3
= 1 2/3</span>
x and x+4 are the numbers
3x=2(x+4)
3x=2x+8
3x-2x=8
x=8
x+4=12
Ok so first we find the equation that equals one variable.
2y = -x + 9
3x - 6y = -15
We solve for y.
2y = -x + 9
y = -x/2 + 9/2
Then we plug in this y value into the other equation to keep only one variable so we can solve for it.
3x - 6y = -15
3(-x + 9/2) - 6y = -15
-3x + 27/2 - 6y = -15
-9y + 27/2 = -15
-9y = 3/2
-y = 3/18
y = -3/18
Then we plug in this numerical y-value into the first equation which we found out by solving an equation for y.
y = -x/2 + 9/2
-3/18 = -x/2 + 9/2
-84/18 = -x/2
-x = 9 1/3
x = -28/3
Your answer would be (-28/3, -3/18)
Hope this helps!
Answer:
Explanation:
<u />
<u>1) Horizontal component</u>
The horizontal component is related to the magnitude of the force by the cosine ratio:
Where α in the angle (-10º), Fx is the horizontal component, and | F | is the magnitude of the force (17).
- cos(-10º) = Fx / 17 ⇒ Fx = cos (-10º) × 17 = 16.74
<u />
<u>2) Vertical component</u>
The vertical component is related to the magnitude of the force by the sine ratio:
Where α in the angle (-10º), Fy is the vertical component, and | F | is the magnitude of the force (17).
- sin(-10º) = Fy / 17 ⇒ Fy = sin (-10º) × 17 = -2.95
<u />
<u>3) Form (x,y)</u>